Clinical Evaluation and Management of Post Burn Flexion Contractures of Fingers: A Prospective Observational Study - GB Karthik; KC Shivamurthy; Suhas Narayanaswamy Gowda; Kosuri Deepak Varma (International Journal of Anatomy Radiology and Surgery, 2025)
Introduction: The management of post burn sequelae of the hand, such as contractures and deformities, is of particular significance in developing countries due to delayed presentations and non compliance with treatment. Aim: To assess the appropriate choice of reconstruction for post burn flexion contractures of the fingers and its functional outcome. Materials and Methods: This prospective observational study included 45 patients with post burn flexion contractures of the fingers over a duration of three years, from March 2021 to February 2024, in the Department of Plastic and Reconstructive Surgery at SSIMS & RC, Davangere, Karnataka, India. Patients were evaluated for age, etiology of burns, duration since the burns, grade of contracture, choice of reconstructive procedure, and functional outcome in terms of the degree of extension achieved. Descriptive statistics were used, and results were expressed in terms of frequency and percentages. Results: Out of total patients, 16 (35.5%) patients belonged to the age group of 1-10 years, and 14 (31.1%) patients were aged 11-20 years. Flame burns accounted for 24 (53.3%) patients. Thirty-six (80%) patients had grade III contractures. Fifteen (33.3%) patients were operated on between six and 12 months post burn, while 19 (42.2%) patients were operated on more than 24 months post burn. A total of 28 (62.2%) patients were affected on their dominant hand, restricting their activities of daily living. Contracture release and Split-Thickness Skin Grafting (STSG) were performed in 18 (40%) patients, while release and Full-Thickness Skin Grafting (FTSG) were performed in 14 (31.1%) patients. Functional improvement in the form of full extension of the fingers was achieved after contracture release in 44 (97.8%) patients. In 1 (2.2%) patient, residual flexion of 10 degrees was noted at the distal interphalangeal joint. Recontracture developed in 1 (2.2%) patient due to irregular follow-up and non-compliance to usage of splint and physiotherapy. Conclusion: The majority of cases of post burn flexion contracture were noted in the paediatric age group. Contracture release and coverage with skin grafting, followed by strict postoperative splinting and physiotherapy, provided a good functional outcome.